2015
DOI: 10.1109/lpt.2014.2385067
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Phase-Shifted Long-Period Fiber Grating and Its Application to Strain Measurement

Abstract: Several kinds of phase-shifted long-period gratings (LPGs) have been fabricated using a high-repetitionrate CO 2 laser, where both the grating and the inserted phase shift are simultaneously produced in a commonly used single-mode fiber. Furthermore, using one of the fabricated phase-shifted LPGs, a temperature-insensitive sensor that allows for large axial strain measurement with a value up to 7600 με, is proposed and first demonstrated. Measurement accuracy for the strain ranging from 340 to 7600 με is estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The separation change between the two split peaks of SLPFGs exhibited a high strain sensitivity of about 106.7 pm/με [61]. Moreover, using a phase-shifted SLPFG fabricated by CO 2 laser beam, a temperature-insensitive sensor that allows for large axial strain measurement with a value up to 7600 με is demonstrated [62]. Ren et al developed a strain sensor with a sensitivity of 1.2 pm/με based on a microtapered SLPFG fabricated by periodically tapering a SMF with CO 2 laser heating source [63].…”
Section: Strain Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The separation change between the two split peaks of SLPFGs exhibited a high strain sensitivity of about 106.7 pm/με [61]. Moreover, using a phase-shifted SLPFG fabricated by CO 2 laser beam, a temperature-insensitive sensor that allows for large axial strain measurement with a value up to 7600 με is demonstrated [62]. Ren et al developed a strain sensor with a sensitivity of 1.2 pm/με based on a microtapered SLPFG fabricated by periodically tapering a SMF with CO 2 laser heating source [63].…”
Section: Strain Sensorsmentioning
confidence: 99%
“…Various heating-induced LPFGs in conventional fiber [12,13,22,28,35,46,47], photonic crystal fiber (PCF) [14,15,16,29,48], and photonic bandgap fiber (PBF) [27,30,31] could then be successfully written. LPFG-based devices have recently attracted great attention and found versatile applications, such as in all-fiber orbital angular momentum (OAM) mode converters [11,13,14,17,49,50,51,52,53,54,55,56], and strain [48,57,58,59,60,61,62,63,64], pressure [16,29,30,65,66], torsion [16,19,38,46] and biochemical sensors [67,68,69,70,71,72,73].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the sensitivity of the I-LPFG strain sensor was −5.62 pm/με. In 2015, Wang et al [ 8 ] proposed phase-shifted LPFG fabricated by CO 2 laser for strain measurement. Three kinds of phase-shifted LPGs with phase shifts of 0, 0.5π, and 1.0π respectively, were fabricated.…”
Section: Introductionmentioning
confidence: 99%
“…Cladding modes play an important role in realizing fiber-optic sensors based on LPFGs with high sensitivity to external perturbation change, such as temperature and strain [1][2][3]. There is much research on the development of fabrication techniques of LPFGs [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. A conventional LPFG can be simply fabricated by exposing single-mode fibers (SMFs) with a germanium-doped core to UV excimer lasers and frequency-doubled argon lasers [1].…”
Section: Introductionmentioning
confidence: 99%
“…A conventional LPFG can be simply fabricated by exposing single-mode fibers (SMFs) with a germanium-doped core to UV excimer lasers and frequency-doubled argon lasers [1]. For specialty fibers without photosensitivity, such as photonic crystal fibers (PCFs), different fabrication techniques are required to generate the periodic index modulation for the realization of LPFGs [2,[6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The etching method to induce the periodic deformation of the silica cladding in the dispersion-shifted fiber (DSF) was proposed by using a hydrofluoric acid (HF) solution incorporating the metal coating procedure [16].…”
Section: Introductionmentioning
confidence: 99%